Cloud-cloud collision in the Sgr B2 molecular cloud complex. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Tsuboi, Masato; Miyazaki, Atsushi; Handa, Toshihiro
Abstract: We present results from a high-resolution wide-field imaging observation of the central molecular zone (CMZ) in H 13 CO + J = (1 − 0) and SiO v =0, J = (2−1) emission lines by using the Nobeyama 45-m telescope in order to depict the high-density molecular gas mass distribution and explore molecular gas affected by interstellar shocks. We found a candidate for ongoing cloud-cloud collision in the Sgr B2 complex. This is identified as a hollow paraboloid-like structure in the l−b−v data cube of both emission lines. The central part of the feature is denser and warmer than the outer envelope and contains a vast amount of shocked molecular gas. These properties are consistent with those expected from simulations of cloud-cloud collisions in the CMZ.